2021
DOI: 10.3390/ma14237332
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Transmission Electron Microscopy Investigation of Melting/Evaporation Kinetics in Anisotropic Gold Nanoparticles

Abstract: We report on thermal stability and phase transition behaviors of triangular Au nanoprisms through in situ heating transmission electron microscopy. With rising temperature, Au nanoprisms exhibit fluctuating surface reconstructions at the corner regions. When a quasi-melting state is reached at the temperature below bulk melting points, the evaporation is initiated commonly at a corner with low curvature and containing sharp intersection points. The subsequent annealing process leads to the gradual evaporation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This partial deformation of the Au NP shape is attributed to the high temperature that is required for the calcination of g-C 3 N 4. Temperature sensitivity and reshaping of Au nanostructures were previously reported in the literature. , …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This partial deformation of the Au NP shape is attributed to the high temperature that is required for the calcination of g-C 3 N 4. Temperature sensitivity and reshaping of Au nanostructures were previously reported in the literature. , …”
Section: Resultsmentioning
confidence: 70%
“…Temperature sensitivity and reshaping of Au nanostructures were previously reported in the literature. 57,58 2.4. Nanohybrid Structural Characterization.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, most of the experiments were performed at constant temperature after initiation of evaporation/sublimation. Therefore, the rate of evaporation/sublimation of nanoparticle was slower in those cases [38,41,45].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, evaporation of Au nanoparticles occurred above 950 °C as confirmed by ex situ and in situ studies. In recent work, Liu et al found that melting/evaporation of prismshaped Au nanoparticles took place at 875 °C using commercial heating chips [38]. Hobbs calculations showed that the temperature rise due to electron beam-induced heating is negligible in highly conductive samples [39].…”
Section: Discussionmentioning
confidence: 99%